1996
DOI: 10.1128/aem.62.12.4318-4322.1996
|View full text |Cite
|
Sign up to set email alerts
|

Complete microbial degradation of both enantiomers of the chiral herbicide mecoprop [(RS)-2-(4-chloro-2-methylphenoxy)propionic acid] in an enantioselective manner by Sphingomonas herbicidovorans sp. nov

Abstract: Sphingomonas herbicidovorans MH (previously designated Flavobacterium sp. strain MH) was able to utilize the chiral herbicide (RS)-2-(4-chloro-2-methylphenoxy)propionic acid (mecoprop) as the sole carbon and energy source. When strain MH was offered racemic mecoprop as the growth substrate, it could degrade both the (R) and the (S) enantiomer to completion, as shown by biomass formation, substrate consumption, and stoichiometric chloride release. However, the (S) enantiomer disappeared much faster from the cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
60
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(68 citation statements)
references
References 19 publications
8
60
0
Order By: Relevance
“…The (S) enantiomers of mecoprop and dichlorprop, structural analogues of the compounds investigated in this study, are biodegraded before or faster than the corresponding (R) enantiomers in soil and sewage sludge [5,7,20,22]. In one of the studies [7], it was shown that sewage sludge that was acclimatized to pure (R)-mecoprop preferentially degraded the (R) but not the (S) enantiomer within 20 h of incubation; this indicated a selective enrichment of speci¢c populations or regulatory changes in speci¢c strains.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The (S) enantiomers of mecoprop and dichlorprop, structural analogues of the compounds investigated in this study, are biodegraded before or faster than the corresponding (R) enantiomers in soil and sewage sludge [5,7,20,22]. In one of the studies [7], it was shown that sewage sludge that was acclimatized to pure (R)-mecoprop preferentially degraded the (R) but not the (S) enantiomer within 20 h of incubation; this indicated a selective enrichment of speci¢c populations or regulatory changes in speci¢c strains.…”
Section: Discussionmentioning
confidence: 91%
“…In order to test and understand the microbial degradation of racemic mixtures of chiral organic compounds, the DOC measurements need to be complemented by enantiomer-speci¢c analysis, because the length of the lag phases as well as the degradation rates may di¡er for the enantiomers. We have reported previously the enantioselective degradation of the chiral herbicides mecoprop [(RS)-2-(4-chloro-2-methylphenoxy)propanoic acid] and dichlorprop [(RS)-2-(2,4-dichlorophenoxy)propanoic acid] by Sphingomonas herbicidovorans MH [5,6] and upon incubation with aerobic sewage sludge [7]. Both the (R) and the (S) enantiomers were completely metabolized but the (S) enantiomers were removed from the test medium before the (R) enantiomers.…”
Section: Introductionmentioning
confidence: 99%
“…The enantioselective degradation of racemic (R/S)-2-(4-chloro-2methylphenoxy)propionic acid (mecoprop) by Sphingomonas herbicidovorans sp. has been reported (Zipper et al, 1996). Growth experiments have demonstrated that (S)mecoprop was degraded first and when it was spent the organism started to degrade (R)-mecoprop.…”
Section: Discussionmentioning
confidence: 94%
“…It has been shown that the configuration of a chiral carbon atom next to the ether bond influences the enzyme-catalysed degradation processes. The microbial attack of chiral ether bonds has been found to be stereoselective and the enzymes differ in their enantioselectivity (Zipper et al, 1996). The enzymes involved in the initial breakdown of chiral phenoxyalkanoates have been studied in detail (Fukumori & Hausinger, 1993;Nickel et al, 1997;Westendorf et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, degradation is initiated by cleavage of the ether bond by α-ketoglutarate-dependent dioxygenases showing pronounced substrate specificity. Whereas phenoxyacetates are cleaved predominantly by 2,4-D/α-ketoglutarate dioxygenases (TfdA) [1,2], degradation of the chiral 2-phenoxypropionates requires two enzymes with opposite enantiospecific characteristics [3][4][5][6][7][8]. (R)-2-(2,4-dichlorophenoxy)propionate/ α-ketoglutarate-dependent dioxygenases (RdpA), which attacks the R-enantiomers of 2-phenoxypropionates, is identical in the primary amino acid sequence in Delftia acidovorans MC1, Sphingobium herbicidovorans MH, and Rhodoferax sp.…”
Section: Introductionmentioning
confidence: 99%